Correctional Social Work: Existence and Legal Intervention in the Juvenile Justice System in Indonesia - Willya Achmad (Faculty of Law, Universitas Pekalongan, 2023)
Correctional social work is the process of helping and rehabilitating people who have problems violating the law.This research investigates the important role of correctional social work in the context of the juvenile justice system in Indonesia. The main focus is on the existence and effectiveness of legal interventions carried out in efforts to rehabilitate and reintegrate children involved in legal violations. This research uses a qualitative approach with descriptive methods. The research results confirm that the existence and intervention of correctional social work in the juvenile justice system in Indonesia has a significant impact in supporting the rehabilitation and reintegration of juvenile criminals. The holistic and therapeutic corrective approach applied by social workers helps children understand their mistakes, develops adaptive skills, and motivates them for positive change. Serving as counselors, motivators, experts, therapists, brokers, educators, advocates, and mediators, correctional social workers facilitate children's access to rehabilitation, education, and training programs that meet their needs. By focusing on the interests and welfare of children as the main priority, the existence and intervention of this effectively ensures the protection and provides the necessary support for children involved in the juvenile justice system in Indonesia, guiding them towards positive behavioral changes and achieving a better future. Good.